1988
DOI: 10.1152/ajprenal.1988.255.4.f674
|View full text |Cite
|
Sign up to set email alerts
|

Mesangial cells express PDGF mRNAs and proliferate in response to PDGF

Abstract: Platelet-derived growth factor (PDGF) is a potent mitogen for cells of mesenchymal origin and is released and/or synthesized by platelets, macrophages, endothelial cells, and rat mesangial cells. In the present investigation, we found that human glomerular mesangial cells in culture release a PDGF-like protein which competes for 125I-PDGF binding to human foreskin fibroblasts and is mitogenic for these fibroblasts. The competing and to a lesser extent the mitogenic activities present in the conditioned medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
148
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(150 citation statements)
references
References 0 publications
2
148
0
Order By: Relevance
“…Rat MCs were cultured from glomeruli isolated by differential sieving as previously described (14). Epithelial cells were removed by digestion with collagenase, and glomerular cores were cultured in RPMI (Life Technologies, Inc., Gaithersburg, MD) supplemented with antibiotics and 17% fetal calf serum.…”
Section: Cell Culturementioning
confidence: 99%
“…Rat MCs were cultured from glomeruli isolated by differential sieving as previously described (14). Epithelial cells were removed by digestion with collagenase, and glomerular cores were cultured in RPMI (Life Technologies, Inc., Gaithersburg, MD) supplemented with antibiotics and 17% fetal calf serum.…”
Section: Cell Culturementioning
confidence: 99%
“…Several studies demonstrated that mesangial cells possess specific receptors for a number of vasoactive substances that couple to phospholipase C. Receptors for angiotensin I1 [45,72], vasopressin [27,73], PDGF [74] and LTD4 [75] have been identified on mesangial cells. Binding of these agents to their specific receptors is associated with activation of a phospholipase C that specifically cleaves PIP2 to yield DAG and IP3.…”
Section: Phospholipase C: the Bifurcating Inositol Lipid Signalling Smentioning
confidence: 99%
“…It has been shown that mouse, rat and human glomerular mesangial cells in culture release PDGF which stimulates DNA synthesis in an autocrine manner [11,16,25]. Findings that PDGF receptor expression is up-regulated in kidney rejection and that PDGF production is enhanced in active glomerulonephritis [16,[32][33][34][35] imply an important role for PDGF in immune responses in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Findings that PDGF receptor expression is up-regulated in kidney rejection and that PDGF production is enhanced in active glomerulonephritis [16,[32][33][34][35] imply an important role for PDGF in immune responses in the kidney. Furthermore, antibodies to PDGF inhibit mesangial cell proliferation and matrix expansion seen in rats with mesangial proliferative nephritis induced by an antibody to the Thy-I antigen that is expressed on mesangial cells [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation